Interrelation Between International Currency Exchange Rate Systems and Economical Stability of States - Žilinskis, Žilvinas; Startienė, Gražina (Ekonomika, 2000)
The main requirement of the classical Gold standard to exchange currencies into gold at the set rate and with no limitations, as well as the self-adjustment mechanism, assured nominal stability of economic variables and satisfactory economic growth in most of the countries.Interwar period instability caused big problems violating trust in currencies, the lowest, during all the analysed exchange rale systems, money stock growth, the further deriving widely spread deflation processes, poor growth of real income per capita, while at the same time budgets’ deficits remained quite low.Though at the Bretton Woods fixed exchange rate system gold did not play such as effective role as during the classical Gold standard, it still stipulated comparatively low inflation rate, fast growth of real income and, in most of the countries, low budgets’ deficits. However, the problem of trust, that caused frequent speculative attacks towards currencies of some countries’, was much more furious during the Bretton Woods, than the Gold standard period.The period of strengthening flexible exchange fate system was in particular known for its enormous money stock growth, inflation rale and budget deficit, as well as poor growth of real incomes. A positive trait of the flexible exchange rale system – in the very instable environment and at the presence of very mobile capital flows. there were quite few currency crises occurring, and the occurred ones did not spread widely as before at the fixed currency rates.Seeking for the EU membership, Lithuania, as well as the rest of the Central and Eastern European countries, committed itself to follow the EU Agreement goals, in particular, to accept all the requirements of Economic and Monetary Union, and to introduce Euros as soon as Lithuania is prepared for the step.The fixed exchange rates assured nominal stability of economic variables and satisfactory economic growth in must of the countries. During the period of strengthening flexible exchange rate system, introverted orientation of many countries caused large fluctuations of currency rates, instability of international economy and increased costs of international transactions.